Students in Poland in the face of the fake news phenomenon in the context of the war in Ukraine - Cywiński, Aleksander (Adult Education Discourses, 2024)
The article addresses the proliferation of “fake news” or “disinformation” in the context of the war in Ukraine that began on February 24, 2022, with Russia as the aggressor. While the conflict has been widely covered by both public and private media globally, the certainty of the reported information’s credibility is in question. Fake news is characterized as false or misleading reports on websites or fabricated stories intended for various purposes. The study examines how Polish students acquire information regarding the war in Ukraine via the Internet, with an emphasis on the issue of fake news. This research revolves around twelve survey questions (online) covering aspects such as information-seeking behaviours, source credibility, and fake news verification techniques. The communicative approach was employed in the study, using seven categories to affirm the credibility of information. While the sample presents asnapshot of the student population’s views, it’s not fully representative of all students in Poland. The research provides an overview of the students’ online information consumption habits in the context of the war in Ukraine. There is clear indication of the dominance of digital platforms, especially social networks, in information dissemination. While students demonstrate some level of discernment by considering authorship and source credibility, the reliance on potentially unreliable platforms and a lack of enthusiasm for training to identify fake news pose concerns. Addressing these concerns would require educational institutions to emphasize the importance of digital literacy. Finally, a set of hypotheses useful in further research is proposed.